2003
DOI: 10.1148/radiol.2271020396
|View full text |Cite
|
Sign up to set email alerts
|

Ileocecal Valve: Spectrum of Normal Findings at Double-Contrast Barium Enema Examination

Abstract: The ileocecal valve may show a spectrum of normal findings at double-contrast barium enema examination and may appear as a round, ovoid, or triangular structure with a maximal height of nearly 4 cm. The valve may be large, asymmetric, or smoothly lobulated, even in the absence of tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
2
11
1
Order By: Relevance
“…position of 15% and 7%, respectively (36,37). However, confirmation that a CAD polyp candidate is related to the ICV does not preclude a pathologic condition on or adjacent to the ICV.…”
Section: Ileocecal Valvementioning
confidence: 96%
See 1 more Smart Citation
“…position of 15% and 7%, respectively (36,37). However, confirmation that a CAD polyp candidate is related to the ICV does not preclude a pathologic condition on or adjacent to the ICV.…”
Section: Ileocecal Valvementioning
confidence: 96%
“…Furthermore, there is no consensus regarding the normal size of the valve; studies have reported a normal thickness for each ICV lip of as much as 1.5 cm and an overall maximal height of approximately 4 cm (37,39,40). On the basis of experience from air-contrast barium enemas, histologically normal valves may be large, asymmetric, or smoothly lobulated, making these characteristics generally nonspecific and unhelpful at CT colonography (37).…”
Section: Ileocecal Valvementioning
confidence: 99%
“…It is formed by the protrusion of the circular muscle layer of the distal portion of the terminal ileum into the lumen of the large intestine [2]. This is usually at the level of the first (33%) or second (65%) complete haustral fold [3][4][5], but can occasionally occur as distal as the third haustral fold (2%) [4,5]. It is usually on the medial colonic wall (81-90%), but may occur on the lateral (1-15%) or posterior (3-8%) wall [3,4].…”
Section: Anatomy and Locationmentioning
confidence: 99%
“…Although rigid measurements are not reliable in distinguishing a normal and enlarged ICV [3], it is on average 1.7 cm high (with a range of 1 to 4 cm) [3][4][5] and 2.8 cm wide (range 1 to 6 cm) [4,5]. In addition, 1.5 cm is considered the upper limit of normal for the height of a single lip of the valve [3].…”
Section: Anatomy and Locationmentioning
confidence: 99%
See 1 more Smart Citation